Alternative and Part‐Time Employment Arrangements as a Response to Job Loss - Farber, Henry S. (Journal of Labor Economics, 1999)
I examine the extent to which workers who lose jobs obtain work in alternative employment arrangements, including temporary work and independent contracting, and obtain voluntary or involuntary part‐time work. I find that job losers are significantly more likely than nonlosers to be in both temporary jobs (including on‐call work and contract work) and involuntarily part‐time jobs. I also find evidence that temporary and involuntary part‐time jobs are part of a transitional process subsequent to job loss leading to regular full‐time employment.